Navigating the Digital Realm: The Impact of Social Media on Mental Health and Spiritual Intelligence in Islamic Educational Settings - Ibdalsyah, Ibdalsyah; Maemunah Sa'diyah; Abdu Rahmat Rosyadi; Putri Ria Angelina; Naskiyah (Jurnal Pendidikan Islam, 2023)
Purpose – The study aims to examine the impact of social media use on the mental health and spiritual intelligence of university students, with a focus on the Islamic educational context. It seeks to understand the dual influence of social media as a tool for information and communication and as a potential factor affecting students' mental and spiritual well-being. Design/methods/approach – Employing a quantitative, correlational method, the study analyzes primary data gathered from questionnaires completed by students of the Faculty of Islamic Religion (FAI) at Ibn Khaldun University Bogor. The approach includes descriptive tests, independent sample T-tests, and correlational analysis to evaluate the relationships among social media use, mental health, and spiritual intelligence. Findings – The study uncovers that students display moderate levels of social media addiction and mental health, with corresponding average scores of 34.9 and 34.7. Interestingly, spiritual intelligence is observed to be high, averaging 41.4. Significant differences in spiritual intelligence and mental health are found between FAI students and those from other faculties, suggesting the influence of a religious learning environment. Correlation analysis reveals that social media usage contributes minimally to variations in spiritual intelligence and mental health, pointing towards the significance of other influencing factors. Research implications – The results highlight the critical role of a spiritually nurturing academic setting in fostering student well-being. The moderate impact of social media on mental health and spiritual intelligence offers a gateway for educational institutions to develop digital literacy programs that encourage responsible social media usage. However, the study's design limits the ability to establish causal relationships, and its findings, specific to the UIKA student body, may not fully extend to other student populations or educational contexts. Future research could explore additional influencing factors, possibly through longitudinal studies, to enhance understanding of causality and broaden the applicability of findings across diverse educational settings.